Pengaruh Kualitas Pelayanan, Fasilitas dan Iklan terhadap Kepuasan Pengunjung Pasar Minggu Kliwon Watu Lumbung Salam Magelang - Setyaningrum, Ratih; Sumarni, Murti; Basri, Anindita Imam (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2022)
The research was conducted in Magelang Regency, Central Java. Focusing on Carikan Hamlet, Kadiluwih Village, Salam District, Magelang Regency, in the 2020/2021 school year. This study aims to determine the effect of service quality, facilities and advertising on visitor satisfaction at Pasar Minggu Kliwon Watu Lumbung. This research is a research that focuses on the quality of services, facilities, and advertising on visitor satisfaction at Pasar Minggu Kliwon Watu Lumbung. The data collection method in this study used observation and questionnaires through purposive sampling techniques. The samples used were 80 people. Data analysis used t test, F test, and multiple linear regression. The results showed that partially the quality of service and advertisements had a positive and significant effect on visitor satisfaction, while facilities had no effect on visitor satisfaction at Kliwon Watu Lumbung Sunday Market because in reality not all visitors used the facilities provided by the Kliwon Watu Lumbung Sunday Market management, such as toilets. In general, the management committee of the Kliwon Watu Lumbung Sunday Market has provided comfortable public toilet facilities, but visitors are more interested in trying simple toilets owned by local residents who are on the river because they are considered more unique. Simultaneously shows that the quality of service, facilities, and advertising have a significant effect on visitor satisfaction. Adjusted R Square in this study is 0.617.